A probability‐based model to quantify the impact of hydropeaking on habitat suitability in rivers. (6th September 2022) - Jelovica, Bähar; Marttila, Hannu; Ashraf, Faisal Bin; Kløve, Bjørn; Torabi Haghighi, Ali
Abstract: A negative effect of hydropower on river environment includes rapid changes in flow and habitat conditions. Any sudden flow change could force fish to move towards a refuge area in a short period of time, causing serious disturbances in the life cycle of the fish. A probability‐based model was developed to quantify the impact of hydropeaking on habitat suitability for two fish species, brown trout ( Salamo trutta ) and Grayling ( Thymallus thymallus ). The model used habitat preference curves, river velocity and depth to develop the suitability maps. The suitability maps reveal that habitat suitability deteriorates as flow increases in the studied part of the river. The probability model showed that, on average, suitability indices are higher for adult grayling than juvenile trout in hydropeaking events in this part of the river. The method developed shows the potential to be used in river management and the evaluation of hydropeaking impacts in river systems affected by hydropower.